Bleomycin vs Setrol for Sclerotherapy of the Lymphovenous Malformation - B.V. Girish; Nischal Kundaragi; K N Puneeth Kumar (Asian Journal of Medical Radiological Research, 2021)
Introduction: Lymphatic malformations are developmental anomalies of lymphatic system consisting of abnormally formed lymphatic channels and cystic spaces. Bleomycin was first developed as an antineoplastic antibiotic, and its sclerosing effect was discovered later. The mechanism involves damage to endothelial cells with a nonspecific inflammatory reaction and occlusion of vessels. Vascular malformations have devastating cosmetic effects in addition to being associated with pain and bleeding. Sclerotherapy has been used as an effective therapeutic modality for the management of vascular malformations. Subjects and Methods : The material for this study was gathered from the patients treated with sclerotherapy for vascular malformation in the Sapthagiri Institute of Medical Sciences and Research Centre from January 2020 to December 2020 in the Department of Interventional Radiology. The material covers for 63 consecutive patients. The journals of each patient were examined for the following factors: age, medical specialty in charge of treatment, sporadic or familiar malformation, single or multiple and anatomic lesions, any prior treatment, type of radiological imagining, nature of the malformation (venous, lymphatic, venolymphatic, capillary or arteriovenous), smoking, number of sclerotherapies, nature of the sclerosant that was used (polidocanol, OK-432, ethanol, and glue), complications, and duration (follow-up) of treatment. Result: The 63 patients were divided into two groups: patients that eventually underwent a surgical procedure versus patients that did not. Patients were decided to be operated on if the result of the sclerotherapy was regarded as poor. These two patient groups were compared regarding the factors presented above for statically significant differences. Conclusion: Lymphatic malformations are developmental anomalies of the lymphatic system that occur most commonly in the head and neck region followed by axilla and mediastinum. The precise aetiology of LMs is still unknown. In 50% of cases, they are present at birth with 80% to 90% diagnosed within the first two years of life. Initially they usually present as a painless, soft mass with wide variations in the growth rate. Rapid growth can occur as a result of trauma, intralesional haemorrhage and thrombosis. Spontaneous regression is very rare.